Differences in execution and perception of training sessions as experienced by (semi-) professional cyclists and their coach. Issue 10 (3rd October 2022) - Voet, Jens G.; Lamberts, Robert P.; de Koning, Jos J.; de Jong, Jelle; Foster, Carl; van Erp, Teun
ABSTRACT: This study aimed to investigate whether (semi-)professional cyclists' execution of a training programme differs from the coach's designed training programme. Also, the study sought to ascertain, in instances where the training sessions were indeed executed as designed by the coach, whether the perception of the cyclists differed from the intention of the coach. This study highlights the differences between the coach and the individual cyclist. In total, 747 training sessions were collected from 11 (semi-)professional cyclists. Rating of Perceived Exertion (RPE) and session Rating of Perceived Exertion (sRPE) were compared with intended RPE (iRPE) and intended sRPE (isRPE), planned by the coach. Pearson's correlation, regression coefficients and Typical Error of Estimate (TEE) were used to identify differences between the executed and planned training sessions. Moderate to large TEEs were noted between executed and intended sRPE, which indicates that cyclists do not always execute the training programme planned by the coach. Furthermore, when the training was executed as planned by the coach, v ery large correlations but moderate to very large TEEs were noted between cyclists' (s)RPE and the coach's i(s)RPE, with unique individual regression coefficients. This indicates that the relationship between RPE and iRPE is unique to each cyclist. Both the different execution and perception of the training programme by the individual cyclists could cause an impaired training adaptation. Therefore, the coach must pay attention to the perception of training sessions by the individual cyclist. Improved individual management of training load could result in the optimisation of the proposed training programme.